DETERMINATION OF GAS-CONDENSATED FACTORS BASED ON COMPOSITION WITH NEWTON-RAPHSON ITERATION METHOD - Supahar Supahar (Jurnal Penelitian Saintek, 2001)
The purpose  of  this research was  to determine z-factor  of gascondensate system using an iterative Newton-Raphson method to solve the Soave-Redlich-Kwong cubic equation of state (SRK CEOS). In this study, some influencingfactors  were observed, i.e., compositions of hydrocarbon, temperature, and pressure  of the gas condensate  system.  The  research  method  involves determination process  of the  Hepthane plus  characteristic.  i.e. Critical  Temperature  of  C7+  (T; C7+),   critical pressure  of  C7+ (PcC7+). and acentricfactor of Cv; (COC7+) using Riazi and Duabert equation;  and  the flash   liberation  process   to  determine  the compositions  of  hydrocarbon  gas  at  certain pressure   (P) and temperature  (T).    Comparison of the z-factors  calculated  using Newton-Raphson method to solve the SRK-CEOS  with modified Dranchuk   Abou-Kassem  equation  and Standing-Katz  method yield an average different of  0.3419 percent and 1.13 percent.